2018
DOI: 10.36076/ppj.2018.5.e533
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Perceptions of Chronic Pain During the Economic Crisis: Lessons Learned from Greece

Abstract: Background: Chronic pain is well known to be influenced by various social factors; however, the impact of financial issues on pain has not been extensively studied. Objective: The aim of this study was to investigate the impact of the economic crisis on pain and quality of life in Greek patients suffering from chronic pain. Study Design: The study employed a prospective, open-label design. Setting: The study setting was the Pain Unit of Attikon University Hospital in Athens, Greece. Methods: The study surveyed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 23 publications
1
13
0
1
Order By: Relevance
“… 59 , 60 This is an added weight to the Greek population who have only just emerged from a decade of recession and a subsequent significant impact on patients’ pain levels and quality of life. 20 Lastly, (6) the long-term pain effects of ICU treatment or secondary diseases and parainfectious pain due to Covid-19 infection are currently under the microscope and remain to be seen. 61 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 59 , 60 This is an added weight to the Greek population who have only just emerged from a decade of recession and a subsequent significant impact on patients’ pain levels and quality of life. 20 Lastly, (6) the long-term pain effects of ICU treatment or secondary diseases and parainfectious pain due to Covid-19 infection are currently under the microscope and remain to be seen. 61 …”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was developed based on the one used and validated in a previous study by the same team to assess the impact of the economic crisis on chronic pain patients. 20 , 28 It was further modified to assess the new problems that accompany the Covid-19 pandemic and subsequent lockdown. The questionnaire has two parts.…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, the economic crisis in Greece may be another factor that influenced the scores in the current study. Even though the impact of financial issues on chronic pain has not yet been extensively studied, there is evidence that the economic crisis in Greece has affected quality of life and pain perception in patients with chronic pain …”
Section: Discussionmentioning
confidence: 99%
“…The duration of treatment was usually over two years, and over half of the patients were given specialist multimodal treatment. It follows from the study of Batisaki et al (2018) done in patients at the pain ward of the Attikon University General Hospital in Athens that the type of pain reported most frequently was located in the area of the lower back (sciatica) and headache [21]. Rockett et al (2013) did research among the patients of a pain management center in Plymouth that indicated that patients most often presented with back pain and secondly musculoskeletal and neuropathic pain [22].…”
Section: Discussionmentioning
confidence: 99%